Densities, viscosities and derived thermophysical properties of water-saturated imidazolium-based ionic liquids - Martins, M.A.R. (Elsevier, 2015)
In order to evaluate the impact of the alkyl side chain length and symmetry of the cation on the thermophysical properties of water-saturated ionic liquids (ILs), densities and viscosities as a function of temperature were measured at atmospheric pressure and in the (298.15-363.15)K temperature range, for systems containing two series of bis(trifluoromethylsulfonyl)imide-based compounds: the symmetric CnCnimNTf2 (with n=1-8 and 10) and asymmetric CnC1imNTf2 (with n=2-5, 7, 9 and 11) ILs. For water-saturated ILs, the density decreases with the increase of the alkyl side chain length while the viscosity increases with the size of the aliphatic tails. The saturation water solubility in each IL was further estimated with a reasonable agreement based on the densities of water-saturated ILs, further confirming that, for the ILs investigated, the volumetric mixing properties of ILs and water follow a near ideal behavior. The water-saturated symmetric ILs generally present lower densities and viscosities than their asymmetric counterparts. From the experimental data, the isobaric thermal expansion coefficient and energy barrier were also estimated. A close correlation between the difference in the energy barrier values between the water-saturated and pure ILs and the water content in each IL was found, supporting that the decrease in the viscosity of ILs in presence of water is directly related with the decrease of the energy barrier. Â© 2015 Elsevier B.V.